The Influence of Live Streaming Strategy and Consumer Behavior on Purchasing Decisions of Fashion Smes on Tiktok Shop - Siti Aninditya; Mulyadi Suhardi (Escalate : Economics and Business Journal, 2026)
TikTok Shop's live streaming drives fashion MSMEs amid Indonesia's social commerce surge. This study examines live streaming strategy and consumer behavior's impact on purchasing decisions using a quantitative survey of 104 purposive-sampled TikTok Shop users buying MSME fashion products. An online ordinal-scale questionnaire was analyzed via non-parametric tests (Spearman correlation, Kruskal-Wallis) and curve estimation. Results show moderate correlation for live streaming (rho=0.512, p=0.000), strong for consumer behavior (rho=0.668, p=0.000), with cubic models yielding R²=0.215 (X1-Y) and R²=0.396 (X2-Y); multicollinearity noted. Both factors synergistically influence decisions, with consumer behavior dominant; MSMEs should optimize interactions and behavioral insights..